2005
DOI: 10.1161/01.res.0000153979.71859.e7
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Fiber Organization in Swine Right Ventricle and Its Impact on Propagation

Abstract: Abstract-Fiber organization is important for myocardial excitation and contraction. It can be a major factor in arrhythmogenesis and current distribution during defibrillation shocks. In this study, we report the discovery of a previously undetected thin epicardial layer in swine right ventricle (RV) with distinctly different fiber orientation, which significantly affects epicardial propagation. Experiments were conducted in isolated coronary-perfused right ventricular free wall preparations (nϭ8) stained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 35 publications
6
45
1
Order By: Relevance
“…An iterative Jones calculus based algorithm was applied to extract the depth-resolved optic axis for mapping the fiber orientation [13]. The fiber orientation measured is between [-90°, 90°] and represents the projected orientations within the plane perpendicular to the incident light [8,14], which is analog to the "helix" angle measured in DTI [2,7]. The system has a 12.4 µm lateral resolution at the focus and a 5.9 µm axial resolution in tissue.…”
Section: Opt Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…An iterative Jones calculus based algorithm was applied to extract the depth-resolved optic axis for mapping the fiber orientation [13]. The fiber orientation measured is between [-90°, 90°] and represents the projected orientations within the plane perpendicular to the incident light [8,14], which is analog to the "helix" angle measured in DTI [2,7]. The system has a 12.4 µm lateral resolution at the focus and a 5.9 µm axial resolution in tissue.…”
Section: Opt Systemmentioning
confidence: 99%
“…However, in addition to its high system cost, the limited spatial resolution of DTI makes it extremely challenging for revealing detailed myocardial fiber structure in the small mouse hearts. A typical mouse heart has a diameter of ~6 mm with 1~2 mm thick ventricular wall and the myofiber orientation can change over 100° across the thin ventricular wall [6,7]. Abrupt orientation changes of more than 50° were observed between different epicardial layers [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, abrupt fiber direction discontinuities through the wall are documented [8,16]. That can trigger complex propagation patterns [20] which are suspected to be a substrate for arrhythmia [12]. In order to introduce these three-dimensional (3D) heterogeneities in the surface formulation, models with several surfaces have been heuristically proposed [6].…”
Section: Introduction Initially Introduced Inmentioning
confidence: 99%
“…It was also shown that the morphology of optical AP changes with the change in the direction of the wave front propagation, because of the complex anisotropy of the myocardium [19]. However, in their study, the authors obtained the fiber orientations (on a 3D slab of tissue) via histology.…”
Section: Discussion and Future Workmentioning
confidence: 99%